Keefektifan Model Problem Based Learning Berbantuan Concept Mapping Pada Materi Sistem Reproduksi Manusia Untuk Meningkatkan Literasi Sains dan Keterampilan Berdiskusi Kelompok Siswa SMA - Laily Maulida Meidiana; Kartika Ratna Pertiwi (Postgraduate, University of Mataram, 2024)
The learning process consists of a sequence of instructional and learning exercises designed to ascertain the efficacy of concept mapping-aided problem-based learning model on the human reproduction system in raising science literacy as well as the efficacy of the model on the human reproduction system in raising students' discussion skills at SMAN 1 Kasihan. This research employed a quasi-experiment design. The samples of this research were selected using random cluster sampling, consisting of 1 control class used scientific learning approach and 1 experimental class used Problem Based Learning model and Concept Mapping strategy. A descriptive and inferential statistics Independent Sample T-test were employed to analyzed the data. The study's findings indicated that the experimental class's pre-test score was 46.97 and the control class's was 45.53. In addition, the experimental class scored 81.86 on the post-test, whereas the control class scored 62.28. The experimental class has a 0.7 N-Gain score in scientific literacy, whereas the control class has a 0.4 score. Based on the Independent Sample T-test findings, p=0.000 (p<0.05) is the significance threshold. It can be stated that students at SMA N 1 Kasihan's science literacy and group discussion abilities are successfully increased by Concept Mapping-aided Problem Based Learning (PBL) model on human reproduction material.